2021
DOI: 10.3758/s13423-021-01993-y
|View full text |Cite
|
Sign up to set email alerts
|

Contested science: Individuals with higher metacognitive insight into interpretation of evidence are less likely to polarize

Abstract: Societal polarization over contested science has increased in recent years. To explain this development, political, sociological, and psychological research has identified societal macro-phenomena as well as cognitive micro-level factors that explain how citizens reason about the science. Here we take a radically different perspective, and highlight the effects of metacognition: How citizens reason about their own reasoning. Leveraging methods from Signal Detection Theory, we investigated the importance of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
2
16
1
Order By: Relevance
“…Although the literature on this topic is sparse, there are some studies that link individual metacognitive abilities to beliefs or belief formation about societal and political topics Rollwage et al, 2018;Said et al, 2021), which constitute the idea of metacognitive abilities to be associated with climate change attitudes and the effectiveness of the consensus messaging process. One important metacognitive aspect discussed in this literature is confidence in knowledge, which indicates how certain a person is about the accuracy of his or her own knowledge.…”
Section: Metacognition As Moderator Variable In the Gateway Belief Modelmentioning
confidence: 99%
“…Although the literature on this topic is sparse, there are some studies that link individual metacognitive abilities to beliefs or belief formation about societal and political topics Rollwage et al, 2018;Said et al, 2021), which constitute the idea of metacognitive abilities to be associated with climate change attitudes and the effectiveness of the consensus messaging process. One important metacognitive aspect discussed in this literature is confidence in knowledge, which indicates how certain a person is about the accuracy of his or her own knowledge.…”
Section: Metacognition As Moderator Variable In the Gateway Belief Modelmentioning
confidence: 99%
“…While it seems reasonable to assume that misinformation may cause the impairment in metacognitive insight and consequent reductions in health-protective behaviours as effects, in principle the causality could be reversed: people with better metacognitive ability may be less influenced by misinformation. Indeed some studies have reported that lower metacognitive ability is associated with holding radical beliefs and with displaying tendencies toward polarization and dogmatism (Rollwage et al, 2018;Said et al, 2021;Schulz et al, 2020). Based on this interpretation one would expect that health-protective behaviours be associated also with metacognitive insight in general science, and not just with metacognitive insight specifically around COVID-19 knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Summaries varied in the direction of evidence: Either supporting or rejecting the anthropogenicity of climate change (four summaries supporting, four summaries rejecting). Four of the summaries about climate change were adapted versions taken from previous research (two endorsing, two rejecting; Fryer et al, 2019; Said et al, 2021) that had been pretested for comprehensibility (see Said et al (2021) for a description of the pretests); the other four summaries were newly developed to adhere to the same length and structure. All summaries were structured as follows: (a) two introductory sentences describing the aim of the study; (b) three to four sentences describing the findings of the study; and (c) one final sentence stating the conclusion of the study.…”
Section: Methodsmentioning
confidence: 99%